Police Role Big City of Semarang in Vigilantism (Eigenrechting) Prevention by Society - Donny Eko Listianto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The violence that is rife today one of which is an act of vigilantism. Police as law enforcement officers play an important role in the response to vigilantism. Problems in this study were analyzed using role theory and the theory of criminal prevention. Semarang Polrestabes role in the response to vigilante violence committed by groups of people is to undertake pre-emptive, preventive and repressive. Preemptive effort is socialization and approach to society, while preventive measures are done by counseling or routine patrol. A repressive measure is a law enforcement efforts through a series of investigative actions until the submission of the dossier to the level of prosecution that the prosecutor's office. Internal obstacles that arise in the response to vigilante violence is the lack of personnel Satreksim, the concern experienced by police in law enforcement and the difficulty in calling witnesses. To overcome these obstacles with the addition of personnel and coordinate with the nearest police-police. The external resistance is distrust of the justice system, the spontaneous nature of the group of people who come from social pressure factors, the absence of mediator or parties who try to block such vigilante action. To overcome external obstacles to build partnerships with the community, especially the community leaders, religious leaders, youth leader, in the form of law sicialization dan another activities that can made the harmonization dan society understanding. Keywords: Prevention; Vigilantism